Opening a pharmacy under franchise within the statutory prohibition against pharmacy concentration - Michał Jachowicz; Michał Kobylarz (Polish Pharmaceutical Society, 2023)
This article aims to analyze the current jurisprudence of administrative courts in the context of the statutory prohibition against pharmacy concentration, as referred to in Art. 99 sec. 3 point 2 of the Pharmaceutical Law. Determining the guidelines and principles for interpreting the content of the prohibition of concentration is crucial for resolving cases before the State Pharmaceutical Inspection authorities regarding the issuance or transfer of permits for operating public pharmacies. In the practical dimension of interpreting the content of the prohibition of pharmacy concentration, the practice of conducting pharmacy activities within a business model shaped and provided by another entrepreneur, i.e. based on a franchising agreement, is particularly relevant. Entering into a franchising agreement, due to its specific provisions, may result in the recognition of dependence of the franchisee on the franchisor in a manner that qualifies the franchisee as a controlled entity. This assessment, in particular, can be derived from the overall legal and factual circumstances arising cumulatively from the provisions of the franchising agreement and other accompanying agreements. It should be emphasized that the mere fact of entering into a franchising agreement does not directly categorize the assessment of the franchisor's acquisition and exercise of control over the franchisee, and thus does not itself justify the conclusion that the franchisee has been deprived of the independence and economic distinctiveness required under Article in Art. 99 sec. 3 point 2-3 of the Pharmaceutical Law , thus becoming a member of the franchisor's capital group or at least its subsidiary. However, such an assessment may be justified by the analysis of the provisions of the franchising agreement, which - due to the unspecified nature of the agreement - remain to a significant extent determined by the will of the parties, which in business terms may often mean a significant influence of the negotiating dominant party, i.e. the franchisor. In addition, the provisions of other agreements concluded between the parties to the franchising agreement may also be relevant to the assessment, creating a scope of obligations somewhat separate, but in essence directly affecting the overall legal situation of the franchisee, including the closer subordination of the franchisee to the influence and rights of the franchisor, and the scope of control exercised by the franchisor.